A Scoping Review of Educational Intervention on Feeding Practice for caregivers to Support Eating and Drinking Ability of Children with Cerebral Palsy - Sagita, Desita Ike; Salimo, Harsono; Andayani, Tri Rejeki (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
Children with cerebral palsy (CP) have eating and drinking difficulties, so caregivers should have knowledge and skills about feeding practice. Education to caregivers about feeding practice aims to support children with CP to be able to eat and drink safely and efficiently. Feeding practice about diet, food consistency, food variety, and appropriate eating and drinking utensils for children with CP can support their functional ability in receiving food and drinks. The method used was the scoping review of articles obtained from PUBMED, Science Direct, and Google Scholar database. The articles obtained were then selected using the article selection diagram. This review focused on feeding practice educational intervention for caregivers to support the eating and drinking ability of children with CP. The results showed that the caregivers’ knowledge and skills in carrying out the feeding practice could increase the safety, time efficiency, and eating and drinking ability of children with CP.